A novel UV-emitting phosphor: Li6CaB3O8.5:Pb2+ - BAŞAK, ALİ SADİ (ELSEVIER, 2011)
Pure Li6CaB3O8.5 and Li6Ca1-xPbxB3O8.5 (0.005 <= x <= 0.04) materials were prepared by a solution combustion synthesis method. The phase of synthesized materials was determined using the powder XRD and FTIR. The synthesized materials were investigated using spectrofluorometer at room temperature. The emission and excitation bands of the synthesized phosphors were observed at 307 and 268 nm, respectively. The dependence of the emission intensity on the Pb2+ concentration for the Li6Ca1-xPbxB3O8.5 (0.005 <= x <= 0.04) was studied and observed that the optimum concentration of Pb2+ in phosphor is 0.01 mol. The Stokes shift of the synthesized phosphor was calculated to be 4740 cm(-1). (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Li6CaB3O8.5; Inorganic borate; Photoluminescence; PHOTOLUMINESCENCE CHARACTERISTICS; PHASE-RELATIONS; PB2+; LUMINESCENCE; SPECTRA